2007
DOI: 10.1177/0093854807299543
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Incarceration On Intimate Relationships

Abstract: Although incarceration has a substantial impact on intimate relationships, little is known about how individuals cope with their separation and reunification. Incarceration also poses serious health risks for HIV infection, as rates are up to 6 times higher in the prison than the general population. A series of focus groups were conducted with individuals affected by incarceration to examine specific relationship challenges and factors that may place them at increased risk for HIV infection during and after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 51 publications
(57 reference statements)
5
77
1
1
Order By: Relevance
“…Our results suggest that pre-release interventions focused on maintaining and strengthening social ties to loved ones in the community, particularly ties to significant others, during incarceration may help reduce HIV sexual risk behaviors during community re-entry. Our findings expand those of previous studies to delineate the independent effects of different sources of support on sexual risk-taking [7,12,18,19] and support extant studies highlighting the importance of [23,24,45,46]. By directly comparing distinct sources of support, the current study has been able to underscore the salience of significant other support in reduced HIV risk.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results suggest that pre-release interventions focused on maintaining and strengthening social ties to loved ones in the community, particularly ties to significant others, during incarceration may help reduce HIV sexual risk behaviors during community re-entry. Our findings expand those of previous studies to delineate the independent effects of different sources of support on sexual risk-taking [7,12,18,19] and support extant studies highlighting the importance of [23,24,45,46]. By directly comparing distinct sources of support, the current study has been able to underscore the salience of significant other support in reduced HIV risk.…”
Section: Discussionsupporting
confidence: 85%
“…Members of our group and others have observed that having a significant other is strongly associated with protection against sexual risk-taking behaviors such as multiple and concurrent partnerships before incarceration and after release; however, the effects of other sources of support on sexual risk-taking were not assessed [23][24][25]. Significant other support may offer particularly strong protection against sexual risktaking compared to other forms of support, and those who do not return home to a significant other after prison release may seek new and/or multiple partners to meet companionship or financial needs [19].…”
Section: Introductionmentioning
confidence: 99%
“…Harman et al (2007), for example, use evidence sourced from wives of incarcerated prisoners who are affronted and dismayed at the degree of free time and relaxation that their male partners enjoy when in prison, at precisely the time when they are having to manage both the family finances and the children themselves. Furthermore, May and Woods (2005) demonstrate that many American prisoners would prefer to go to prison than do community service, house arrest or 'boot camp' when offered the choice.…”
Section: Prisoners = 'Not Good Citizens'mentioning
confidence: 99%
“…41 Incarceration affects sexual relationships directly through the removal of a partner and the emotional and material support they provided, 42 which may lead non-incarcerated partner to experience emotional distress and financial challenges. 43 In addition, when children are involved, the non-incarcerated partner may have increased child care-giving burden. 44 This experience may shape one's attitudes about incarceration and having relationships with incarcerated individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been previously reported. 43 It is important to note that we did examine the relationships between attitudes and norms with having unprotected sex with partner after release. However, there was no significant association (data not shown).…”
mentioning
confidence: 99%